Long-lag morphological priming and inflectional paradigm size effects in Estonian and Finnish text reading - Lõo, Kaidi; Bertram, Raymond; Kuperman, Victor (John Benjamins Publishing Company, 2026)
Morphological priming and paradigm size effects have been established in single word reading studies, however, morphological priming effects in longer texts have not been observed, and, to the best of our knowledge, paradigmatic effects in text reading have not yet been examined. The current study utilized the Multilingual Eye-Tracking Corpus MECO (Siegelman et al., 2022) to explore paradigmatic and morphological priming effects during text reading in Estonian and Finnish, two morphologically rich Finno-Ugric languages. The results showed clear inflectional paradigm size effects for Estonian during text reading in several eye movement measures, but not for Finnish. This may be linked to the support from the inflectional paradigm being semantically more beneficial to the reader in Estonian than in Finnish. The current study also showed clear long-lag inflectional priming effects in text reading, unlike what was observed in prior studies in Dutch, English, and Spanish. This study is thus the first to show that inflectional priming can extend beyond word or sentence level and suggest that inflectional variants of a particular word in Estonian and Finnish get and remain activated even when text context is present.